Polyembryony and hybrids frequency in Citrus spp. - Soares Filho, Walter dos Santos; Moreira, Célio dos Santos; Cunha, Mario Augusto Pinto da; Cunha Sobrinho, Almir Pinto da; Passos, Orlando Sampaio (Pesquisa Agropecuaria Brasileira, 2000)
Controlled crosses were done by using the mandarins 'Clementine' and 'Sunki', the 'Rangpur' lime and the 'Volkamer' lemon as female parents with none, low, low to moderate and moderate polyembryony degrees, respectively, and Poncirus trifoliata and its hybrids as male parents for its easily recognizable trifoliate characteristic. The hybrid frequencies were 57.4%, 53.6%, 18.6% and 14.2% for 'Clementine', 'Sunki', 'Rangpur' and 'Volkamer', respectively. It was also observed a negative association between polyembryony degree and hybrids frequency.